2021
DOI: 10.1111/jam.15206
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of virulence factors and its relatedness towards the antimicrobial response of enterotoxigenic Escherichia coli strains isolated from patients in Kolkata, India

Abstract: Aim: Enterotoxigenic Escherichia coli (ETEC) is one of the most widely recognized diarrhoeal pathogens in developing countries. The advancement of ETEC vaccine development depends on the antigenic determinants of the ETEC isolates from a particular geographical region. So, the aim here was to comprehend the distribution of virulence determinants of the clinical ETEC strains of this region. Additionally, an attempt was made to find any correlation with the antimicrobial response pattern. Methods and results: Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…ETEC is the most common cause of traveler’s diarrhea and rarely found in meat products, and contaminated food and water have been implicated as vehicles for transmission of ETEC infection. Moreover, ETEC has been studied in India, the United States, and other regions ( Daniels, 2005 ; Crofts et al, 2018 ; Mondal et al, 2022 ). While the amount of ETEC collected in this study was limited and originated from Bangladesh, the United States, China, Chile, and other countries, it was impossible to evaluate the geographical specificity of strains in each region.…”
Section: Resultsmentioning
confidence: 99%
“…ETEC is the most common cause of traveler’s diarrhea and rarely found in meat products, and contaminated food and water have been implicated as vehicles for transmission of ETEC infection. Moreover, ETEC has been studied in India, the United States, and other regions ( Daniels, 2005 ; Crofts et al, 2018 ; Mondal et al, 2022 ). While the amount of ETEC collected in this study was limited and originated from Bangladesh, the United States, China, Chile, and other countries, it was impossible to evaluate the geographical specificity of strains in each region.…”
Section: Resultsmentioning
confidence: 99%
“…CofT has a lysozyme-like domain and produces type 4b pilus CFA/III lytic transglycosylase. CFA/III is a colonization factor antigen (CFA) group that assists the release of enterotoxins by attaching to the epithelium of the small intestine in Enterotoxigenic Escherichia coli (ETEC) [23,24]. Its homology genes, IagB of Salmonella enterica serovar Typhi and IpgF of S. flexneri, participate in the invasion of eukaryotic host cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…In exploring the utility of EtpA as a potential vaccine antigen, studies to date have demonstrated that the etpBAC locus is highly conserved across ETEC from geographically disparate origins [25][26][27][28][29][30] , is immunogenic following natural 27,30 and human experimental challenge 31,32 infections, and that immunization with recombinant EtpA (rEtpA) affords considerable protection against intestinal colonization 21,27,29,33 19,34-37 . In addition, EtpA expression by ETEC strains is strongly associated with the development of diarrheal illness in young children, while antibodies against EtpA are associated with protection 30 .…”
Section: Introductionmentioning
confidence: 99%